E-213 De novo dural arteriovenous fistulas after endovascular treatment: case illustration and literature review. (23rd July 2022) - Dowlati, E; Duquette, E; Felbaum, D; Armonda, R; Liu, A
Abstract : Introduction: Intracranial dural arteriovenous fistulas (dAVF) account for 10–15% of all arteriovenous malformations. Although the majority of dAVF are effectively cured after endovascular intervention, a small proportion of patients may have dAVFs recurrence or de novo formation after radiographic cure. Case Report: We present a case of a 69-year-old female with de novo formation of three dAVFs in different anatomic locations after successive endovascular treatments. Her initial dAVF was identified in the right posterior frontal parafalcine region and obliterated with transvenous Onyx embolization. The patient returned eight years later due to left-sided pulsatile tinnitus and a new dAVF in the left greater sphenoid wing region was seen on angiography. This was treated with transvenous Onyx embolization with complete resolution. One year later, she developed left sided pulsatile tinnitus again and was found to have a left carotid-cavernous dAVF. Given the low intracranial hemorrhagic risk associated with the third dAVF, it was managed conservatively with observation. Discussion: After reviewing the literature, we found 18 cases of de novo dAVF formation after endovascular treatment. Of the 18 cases, 16 had de novo formation of a second dAVF after intervention, however only two cases reported de novo formation of a third metachronous dAVF. Whilst the etiology of de novo dAVF formation is still unclear, they are likely generated by numerous factors stemming from changes in venous flow which trigger the widespread expression of vascular endothelial growth factor resulting in aberrant vascular development. There are multiple methods to treat dAVF, including microsurgery, radiosurgery, endovascular embolization with coils and/or liquid embolic agents. The current gold standard of therapy is endovascular treatment (EVT) with the copolymer Onyx due to the substantial research supporting its efficacy and safety. No cases of metachronous de novo dAVF formation were found with the use of Onyx. Most cases (13/18) had de novo formation of a secondary dAVF after EVT with coils. Here we present a rare case of three metachronous de novo dAVFs and the first with the formation of de novo metachronous dAVFs after EVT with Onyx. Conclusion: Given the evolving treatments available for dAVFs, it is important to have proper follow-up to further understand the relationship between EVT and dAVF formation. Expanding current research on dAVF treatments and outcomes will allow for better prevention of subsequent dural arteriovenous malformations. Disclosures: E. Dowlati: None. E. Duquette: None. D. Felbaum: None. R. Armonda: None. A. Liu: None.